Pathways linking socioeconomic status to small-for-gestational-age (SGA) infants among primiparae: a birth cohort study in China. Issue 6 (14th June 2018) - Luo, Xiu; Liu, Lingfei; Gu, Huaiting; Hou, Fang; Xie, Xinyan; Li, Xin; Meng, Heng; Zhang, Jiajia; Xu, Shunqing; Song, Ranran
Abstract : Objectives: Evidence about the relationship between socioeconomic status (SES) and small-for-gestational-age (SGA) infants was insufficient among Chinese primiparae. In addition, factors that may mediate this relationship are poorly understood. The purpose of this study was to investigate the risk of and mediators between SES and SGA. Design: Retrospective cohort study. Setting: Wuhan, Hubei, China. Method: Participants were recruited from patients who gave birth in the maternity care hospital of Wuhan between September 2012 and October 2014. Logistic regression models were used to estimate the association between SES and SGA. Pathway analysis was performed to examine the contribution of maternal lifestyles and pregnancy-induced hypertension syndrome (PIH) to the relationship between SES and SGA. Total effect, direct effect and indirect effect of SES on SGA were measured. Effect sizes were evaluated by unstandardised estimates (B) and standardised estimates (ß). Results: Among 8737 primiparae, 927 (10.61%) pregnant women had babies with SGA. High SES was inversely associated with risk of SGA (OR 0.856; 95% CI 0.737 to 0.995) after adjustment for potential confounders. Maternal obstetric characteristics, lifestyles and PIH completely mediated SES and SGA (indirect effect: B=−0.067, 95% CI −0.108 to –0.026). The indirect effect of SES was strengthened by PIH (B=−0.029), a multivitamin supplement (B=−0.021), prepregnancy body mass index (BMI) ≥18.50 (B=−0.009) and prepregnancy BMI ≥18.50 to gestational weight gain (GWG) not below the Institute of Medicine (IOM) recommendations (B=−0.003). Conclusions: Women from high SES predicted lower risk of PIH, more chances to take a multivitamin supplement during early pregnancy, keeping prepregnancy BMI ≥18.50 kg/cm 2 and gaining adequate gestational weight which was not below IOM recommendations. Furthermore, lower risk of PIH, more chances to take a multivitamin supplement, prepregnancy BMI ≥18.50 kg/cm 2 and GWG not below IOM recommendations were associated with a lower risk of SGA infants.